The Role of IoT and Emerging Technologies in Shaping Smart Hospitals - Anas, Adhe Sofyan; Alchamdani; Syam, Sadli; Arwan; Firmansyah (Indonesian Scientific Publication, 2025)
Smart hospitals represent a transformative model in healthcare, leveraging Internet of Things (IoT), artificial intelligence (AI), big data, and blockchain to improve operational efficiency and patient safety. This narrative review synthesizes current literature on the implementation and impact of these technologies in hospital environments. The findings show that IoT integration reduces operational redundancies, enhances real-time patient monitoring, and supports predictive analytics to prevent clinical errors. Supporting technologies such as AI and blockchain strengthen data-driven decision-making and secure data management. However, challenges persist, including interoperability issues, cybersecurity risks, and disparities in adoption across regions. The review underscores the importance of policy frameworks, workforce readiness, and governance structures in enabling successful implementation. Future research should prioritize longitudinal and comparative studies to better evaluate the long-term effects of smart hospitals and promote equitable digital transformation in healthcare systems.